Gastrointestinal function and microbiota in endurance athletes - Sumi, Daichi; Suzuki, Yoshio (Frontiers in Physiology, 2025)
The special issue “Physiological Aspects of Marathon Running” in “Frontiers in Physiology” aims to evoke attentions to this field. In this minireview, the two guest editors of the special issue introduce their interest in the gastrointestinal (GI) functions with endurance running and gut microbiota on marathon running. Following the introduction, the first part summarized research examining exercise-induced GI damage and methods to mitigate the damage. The latter part summarized the influence of exercise on gut microbiota, and the gut microbiota on endurance performance. From the brief overview above, this minireview synthesizes current knowledge and identifies critical topics for future studies for optimizing GI function and the gut microbiota in endurance athletes.